Wood properties and uses - Tanaka, Arthur; Davis, John; Classroom Video; Classroom Media (Coquitlam, B.C. : Classroom Video ; Morris Plains, N.J. : Classroom Media, 2001)
This program shows simple tests that can be conducted in the workshop to determine the best wood for a job. Students gain an understanding of how woods differ so that they can judge how to choose the right wood for a particular purpose
Hardness -- Stiffness -- Density -- Glueability -- Toughness -- Finish -- Friction -- Ethics -- Cost -- Color -- Resistance to fungus and termites -- Safety
Title from title screen
Camera, Peter Beeh ; editor, Phil Sheppard ; online-editor, Roddy Balle ; sound, Konrad Skirlis
Narration, Ross Huguet
Grades 7-12
DVD format
Keywords: Woodwork -- Juvenile films